In-vitro Equilibrium Phosphate Binding Study of Sevelamer Carbonate by UV-Vis Spectrophotometry - Prasaja, Budi; Syabani, M. Maulana; Sari, Endah; Chilmi, Uci; Cahyaningsih, Prawitasari; Kosasih, Theresia Weliana (Drug Research, 2018)
Sevelamer carbonate is a cross-linked polymeric amine; it is the active ingredient in Renvela® tablets. US FDA provides recommendation for demonstrating bioequivalence for the development of a generic product of sevelamer carbonte using in-vitro equilibrium binding study. A simple UV-vis spectrophotometry method was developed and validated for quantification of free phosphate to determine the binding parameter constant of sevelamer. The method validation demonstrated the specificity, limit of quantification, accuracy and precision of measurements. The validated method has been successfully used to analyze samples in in-vitro equilibrium binding study for demonstrating bioequivalence.
Keywords: biopharmaceuticals; chemistry; bioavailability; absorption